Quantifying the mechanical work of breathing in men and women during rowing - Reinhard, P. A.; Gerson, E. A. M.; Sheel, A. W.; Archiza, B. (European Journal of Applied Physiology, 2020)
PURPOSE: To quantify the mechanical work of breathing (Wb) during an indoor rowing test in men and women. Additionally, to compare sex-based differences in the Wb and its components through a rowing test.